Introducing Molecular Electronics - Cuniberti, Gianaurelio.; Cuniberti, Gianaurelio.; Fagas, Giorgos.; Fagas, Giorgos.; Richter, Klaus.; Richter, Klaus. (Lecture Notes in Physics,, 2005)
This volume presents a summary of our current understanding of molecular electronics combined with selected state-of-the-art results at a level accessible to the advanced undergraduate or novice postgraduate. This single book comprises the basic knowledge of both theory and experiment underpinning this rapidly growing field. Concepts and techniques such as density functional theory and charge transport, break junctions and scanning probe microscopy are introduced step-by-step and are subsequently used in specific examples. The text addresses a wide range of systems including molecular junctions made of single-molecules, self-assembled monolayers, carbon nanotubes and DNA.